Problems and Learning Solutions for Islamic Culture History Subjects in Madrasah Ibtida’iyah - Wahyuni, Siti; Yuanita, Dianis Izzatul (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The aim of this research is to describe various forms of educational problems in learning the history of Islamic culture at MI along with problem solving or solutions. The method used for this research is a qualitative descriptive approach, examing various scientific papers, relevant booksand reports that are relevant to this research. The results of this research produced several problems experienced by educators when learning the history of Islamic culture, including: 1) the students’ different backgrounds. 2) The media, methods and strategies used are boring. 3) Limitations in infrastructure to support learning. 4) Lack of competence from educators, and 5) Limited time allocation for learning the history of Islamic culture. The solutions that can be applied for educators include: frist. Taking a differentiation approach. Second, educators can use CTL, cooperative learning and discovery learning. Third, educators can utilize facilities that are still suitable forb use. Fourth, educator can carry out training and competency development. Fifth, educators can optimize the time given by using several methods.